2019
DOI: 10.3390/w11050956
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climatic and Non-climatic Factors on Groundwater Levels in the Jinghuiqu Irrigation District of the Shaanxi Province, China

Abstract: A chronic decline of the groundwater levels has become one of the hot issues affecting groundwater resources management. The rising global temperature, the high frequency of extreme weather (higher temperature and stronger evaporation, heavy or less rainfall), and unreasonable management policies have become important driving factors, causing a dynamic change in groundwater levels, in many regions. This study aims to explore the impact of climate and non-climate factors on groundwater levels in the Jinghuiqu i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Fully understanding the variation characteristics of groundwater level is a prerequisite for rational development and utilization of groundwater resources [10][11][12]. It is indicated from many previous studies that groundwater level is affected by many factors, such as hydro-meteorological conditions, ground factors, and human activities [13][14][15][16]. Leblanc et al found that there was a sharp decline in groundwater level in the Murray-Darling basin in Australia from 2000 to 2007 due to the extreme drought [17].…”
Section: Introductionmentioning
confidence: 99%
“…Fully understanding the variation characteristics of groundwater level is a prerequisite for rational development and utilization of groundwater resources [10][11][12]. It is indicated from many previous studies that groundwater level is affected by many factors, such as hydro-meteorological conditions, ground factors, and human activities [13][14][15][16]. Leblanc et al found that there was a sharp decline in groundwater level in the Murray-Darling basin in Australia from 2000 to 2007 due to the extreme drought [17].…”
Section: Introductionmentioning
confidence: 99%
“…The highest anomaly occurred in June 2021 at 171 mm2. Several factors that cause rainfall anomalies include climate change, atmospheric stability, population density, and local topography (Harada et al, 2020;Lakshmi & Schaaf, 2001;Lima et al, 2017;Zhao et al, 2019). Rainfall anomalies in Indonesia significantly impact the agricultural sector, especially food crop production (Dirgahayu et al, 2012).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Academics and governments generally agree that climate change also impacts the dynamic changes in water table depths [15][16][17][18][19]. Prolonged droughts and low levels of rainfall may cause a significant decline in water table depth [20].…”
Section: Introductionmentioning
confidence: 99%